(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
The considerable postharvest losses of papaya during storage, compounded by inadequate postharvest management practices, are alarming in the context of escalating global food insecurity, malnutrition, and environmental impact. Addressing this issue necessitates the development of sustainable preservation strategies. Notably, chitosan-based coating emulsions have exhibited efficacy in preserving the overall quality parameters of papaya, mitigating weight loss when active components are judiciously formulated. The ionic gelation technique was used to obtain the nanoparticles and subsequently, the coating emulsion was formulated by solvent blending . The emulsion coating was applied to the papaya by dipping while the concentration variant impact of acetic acid, Tween 80, and chitosan molecular weight on the weight loss of coated papaya fruits was systematically investigated during an 8-day room temperature storage period. Optimal concentrations were identified, suggesting suitability for acetic acid at 0.6% to 1.0%, Tween 80 at 0.3% to 0.6%, and a preference for 0.5% low molecular weight (LMW)-chitosan. The coating solutions were characterized by using an FTIR spectrometer and a master sizer. Furthermore, kinetic regression analysis revealed adherence to zero-order kinetics, enabling the formulation of predictive models for different samples and the control group. Empirically and statistically, the sample comprising 0.5% LMW-Chitosan, 1.0% Acetic acid, 0.6% Tween 80, 0.3% sodium tripolyphosphate (NaTPP), and 0.3% ginger oil emerged as particularly suitable for preserving the overall quality parameters of papaya during storage.